Reproduction of the mangrove species Rhizophora stylosa Griff. at its southern latitudinal limit - Wilson, Nicholas C.; Saintilan, Neil (Aquatic botany, 2018)
•Rhizophora stylosa reproduces successfully at its southern limit.•This supports vegetative data that the species is not physiologically limited there.•The capacity to convert buds to propagules was relatively high.•Reproductive phenology and length of the reproductive cycle were generally comparable to tropical studies.•Propagule production did not correlate with bud, flower or fruit number on shoots. A study of reproductive phenology and reproductive performance of the mangrove species Rhizophora stylosa was conducted in three estuaries spanning the southernmost 265 km of its known range on the east Australian coast. The timing of reproductive primordia, buds, flowers, fruit and propagule fall did not differ significantly over the latitudinal range of the study. Peak propagule fall occurred in April after a mean 19–20 months of development, only slightly longer than accounts for tropical latitudes. On average, 2.1% of buds matured to form viable propagules, with an average of 17.2% of buds becoming advanced fruit and 11.9% of advanced fruit becoming mature propagules, which compares well with the ranges published accounts for Australian tropical R. stylosa trees. However, there were relatively few buds per inflorescence on recorded shoots in this study, although formal studies on this in the tropics are absent. Within-site variation in bud and propagule production per shoot was greater than variability between sites in many cases, though our sample size was necessarily low due to the rarity of the trees at the southern limit and the detailed recording method. The species reproduces successfully at its known southern limit, with notable comparability to the eastern Australian Tropics. This suggests there is little thermal limitation on reproduction at the southern limit, where there is evidence of slow spread. “Precocious” reproduction as observed for young R. mangle at range limits in North America was not detected.